Empowerment group of Farmer’s wife to reduce the Pesticide Toxicity - Mahyuni, Eka Lestari; Eyanoer, Puteri Chairani; Mutiara, Erna; Lubis, Arfah Mardiana; Syahri, Isyatun Mardhiah (Talenta Publisher, 2019)
Community empowerment is the one of efforts that undertaken as part of the health promotion which aimed to improve public health. In general, one of the phenomena of society which are expected to consume vegetables and fruits in balance quantity and quality. Consumption of vegetables and fruits also become the second destination health measures of GERMAS (Gerakan Masyarakat Sehat). Karo is an area that is synonymous with the world of agriculture and many farming communities are vulnerable to disease because of exposure to the working environment, either physical or chemical. The farming community is also almost no health care and more oriented to produce in optimum. In addition, there are many groups that still non-productive and can be developed, one group of wives of farmers. The solution given in service activities to produce the healthy food like a salad of vegetables and fruits with antioxidant power, antisianin and other nutrients that protect and maintain the farmer’s health from several symptoms of illness due to consumption patterns and patterns of work at risk. Devotion done by brainstorming methods, training and demonstration of manufacture of the product with the target groups of farmers wife. Outcomes targeted is a food product healthy namely Salad Pelangi as food is beneficial to balance the body, nourish and protect the health of the body as well as foods that have anti venom and avoid hypertension, heart disease, diabetes, cancer and chemical effects of occupational risks as farmers. Other outcomes in the form of a scientific article and video activities. The content of Salad Pelangi are choosen from the fruits and vegetable that has the rainbow colour such as tomato, carrot, orange, avocado, jelly, yam, and purple cabbage. All of these has the antioxidant function that could be reduce the pesticide toxicity.